PENGARUH KEPEMILIKAN MANAJERIAL DAN GENDER DIVERSITY PADA DIREKSI TERHADAP TAX AVOIDANCE DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI - Ruth Bae Eliani Harahap (2023)
This research was conducted with the aim of analyzing and ascertaining the effect of managerial ownership and gender diversity in director on tax avoidance with audit quality as a moderating variable. This study also uses profitability and firm size as control variables. This study uses a sample of mining companies that have been listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The sampling technique used in this study was purposive sampling with 75 samples. This research is a type of quantitative research using secondary data in the form of financial reports and company annual reports. Data analysis techniques in this study used model selection tests, classical assumption tests, multiple linear regression tests and hypothesis testing. The results of this study indicate that managerial ownership and gender diversity in directors has no effect on tax avoidance. Then audit quality strengthen the relationship between managerial ownership and tax avoidance, and audit quality weaken the relationship between gender diversity and tax avoidance.